Реалізація наголошених голосних фонем у підготовленому німецькому мовленні - Кузьменко, Тетяна Миколаївна; Kuzmenko, T. M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено якісні та кількісні характеристики наголошених голосних фонем у сучасному німецькому підготовленому мовленні. Уперше проведено комплексний аналіз умов функціонування основних алофонів голосних у різних видах підготовленого мовлення. Зроблено висновок про наявність кількісної та якісної редукції наголошених голосних, ступінь якої збільшується у переказі. The article touches upon qualitative and quantitative features of stressed vowel phonemes in modern German prepared speech. It is necessary to determine the stressed vowel phonemes variability. For the first time the conditions of main vowel allophones’ functioning in different types of prepared speech was analyzed. The results prove qualitative and quantitative reduction of stressed vowels, which increases in the narration. Maximal modified in reading and narration are vowels of middle raising, which can move to high vowels, and high vowels can alternate with middle vowels. Differentiation of vowels according to the horizontal position of the tongue as one of the five vowels differential markers remains stable. Changes in the vertical position of the tongue, the degrees of vowels’ intensity and labialization vary considerably. The opposition of long and short vowels is most unstable.
Realization of stressed vowel phonemes in prepared German speech
Keywords: підготовлене мовлення; prepared speech; наголошені голосні; stressed vowels; кількісні та якісні характеристики голосних; vowels’ qualitative and quantitative features